Preface to Volume 6, Issue 1 (TEST Trento Student Law Review, 2024)
Dear Readers,I am pleased to present to you Volume 6, Issue 1 of the Trento Student Law Review. This issue marks the beginning of the work of a new generation of editors, who, with great enthusiasm and following in the footsteps of their predecessors, are committed to continuing this ambitious project. I wish to express my gratitude to the previous generation of aspiring jurists for the passion and teachings they have imparted. Their commitment and dedication continue to be a source of inspiration and guidance for the future of the TSLR. The generational shift demonstrates the value and necessity of a legal journal like this, capable of addressing the most current and challenging issues of our time.The articles presented in this issue offer an in-depth view of critical topics, treated with academic rigor and innovative perspectives. The authors contribute with analyses aimed at stimulating debate and promoting a greater understanding of contemporary legal challenges.In particular, in the first essay, Setsen Kiyoutes explores the evolution and ambiguities of the crime of "Picking Quarrels and Provoking Trouble" in China, used to suppress dissent and limit freedom of expression.The second article analyzes Deferred Prosecution Agreements as legal instruments for companies to avoid full criminal liability. With a careful analysis, Mauro fragale and Valentina Grilli highlight the advantages and criticism of such agreements and propose legislative changes to improve their transparency and application.Subsequently, Beatrice Pattaro examines the transformation of mafia organizations in the technological era, focusing on how technology and new forms of communication make it more difficult to identify mafia activities.In the fourth essay, Enrico Zonta evaluates the Eu Directive proposal on Corporate Sustainable Due Diligence and its extraterritorial legal implications, questioning whether it represents a legitimate exercise of extraterritorial jurisdiction or an excessive intrusion into the sovereignty of other States.Finally, Camilla Mantese delves into the standard of Most- Favored-Nation Treatment in international investment law, analyzing its history, evolution, and role in promoting equal treatment between foreign and national investors.The Trento Student Law Review wishes to express its most sincere gratitude to the authors for their valuable contributions and for entrusting our editorial board, and to the University of Trento and our Faculty of Law for their continued support.To conclude, I extend my heartfelt thanks to the new board, all the editors and collaborators for their tireless work and dedication in making this publication possible.The collective commitment ensures that our journal continues to be a valuable source of legal knowledge and debate.I wish you a stimulating and fruitful reading experience.Sincerly, Rossella BorellaEditor-in-Chief